1978
DOI: 10.1080/00926237808402999
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in women who were molested as children: One response pattern and suggestions for treatment

Abstract: A common pattern of women who were sexually molested as children and seek treatment for sexual dysfunction is described. The arousal, rather than the orgasmic, component is involved. The reasons for the evolution of this particular dysfunction are discussed. Treatment should extend the period of sensate focus and address the issues of the woman's anger, her need for control, and her guilt. Excellent results can be achieved in helping the patient to experience physical intimacy and the pleasure of sexual arousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…In a survey of undergraduate women, Briere & Runtz (1985, cited in Browne & Finklehor, 1986 found that sexual abuse victims reported experiencing more depressive symptoms during the 12 months prior to the study than did non-abused subjects. When incest victims in therapy are compared with other therapy clients, however, no significant differences have been found in the rates of depression (Herman & Hirschman, 1981 ;Meiselman, 1978).…”
Section: Emotional Reactions and Self-perceptionsmentioning
confidence: 98%
See 4 more Smart Citations
“…In a survey of undergraduate women, Briere & Runtz (1985, cited in Browne & Finklehor, 1986 found that sexual abuse victims reported experiencing more depressive symptoms during the 12 months prior to the study than did non-abused subjects. When incest victims in therapy are compared with other therapy clients, however, no significant differences have been found in the rates of depression (Herman & Hirschman, 1981 ;Meiselman, 1978).…”
Section: Emotional Reactions and Self-perceptionsmentioning
confidence: 98%
“…Finklehor (1.979, cited in Herman & Hirschman, 1981) found that girls whose mothers were frequently absent or ill were twice as likely to be abused as girls whose mothers were present. Russell (1986) reported that 16 per cent of cases of incestuous abuse in her sample 'progressed ' from non-sexual contact and this is also found in father-daughter incest, which progresses to more intrusive and severe acts of abuse (Herman & Hirschman, 1981 ;Meiselman, 1978). In 43 per cent of cases the abuse occurred only once, and in 68 per cent it took place in either the victim's, perpetrator's or a shared home.…”
Section: Characteristics Of Csamentioning
confidence: 99%
See 3 more Smart Citations